Comparative category as the main object of the Kazakh functional grammar (Eurasian Journal of Philology Science and Education, 2015)
In this paper we consider the problem of comparative functional grammar category of the Kazakh language as the main object of the science that studies the phenomenon of functions. Through the indepth review of the scientific concepts of comparative categories, scientific assumptions about word creation are introduced. The author points out that in this area of knowledge there are so many unresolved issues, including the definition of the object of study of comparative categories, scientific and theoretical questions about the metalanguage of this science. In this regard, the construction of the general scientific theory, the disclosure of practical tasks, the definition of the main goal represent one of the primary and urgent problems requiring immediate solutions in modern Kazakh linguistics. The author emphasizes that the peculiarity of functional grammar of the Kazakh language is in complex and integrated approachthat is taken as a basis for semantic categories of grammar and semantic features, combining multilevel language means. The linguistic analysis in this approach is aimed at studying the interaction of elements atdifferent levels on the functional basis. The analyzed unities integrate elements of different levels (within morphology, syntax, in the sphere of function lexis).
Keywords: сomparative category; knowledge; existence; operation; potential function; functionalsemantic field